PENGARUH TERPAAN PROMOSI PENJUALAN DAN TERPAAN ONLINE CUSTOMER REVIEW DI INSTAGRAM TERHADAP MINAT MENGGUNAKAN BRT TRANS SEMARANG - Iqbal Aulia Ahsan; Muhammad Bayu Widagdo; Yanuar Luqman (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
During the COVID-19 pandemic, BRT Trans Semarang experienced a significant decrease in passenger numbers. As they entered the new normal phase, BRT Trans Semarang actively promoted sales through discounts, cashbacks, and special day promotions. Ideally, intensifying these sales promotions can stimulate interest in using BRT Trans Semarang. On the other hand, there were also online customer reviews on Instagram based on passenger experiences after using BRT Trans Semarang. These consumer reviews could be positive or negative, relating to the service quality. This research aims to determine the influence of exposure to sales promotions and exposure to online customer reviews on Instagram on the intent to use BRT Trans Semarang.The research follows an explanatory type with non-probability sampling techniques. The total number of respondents was 50 people, including both males and females aged 14-27 years, residing in Semarang City, who had seen, heard, or read about the sales promotions and consumer reviews on Instagram for BRT Trans Semarang. The analysis used ordinal regression, and the results indicated that exposure to sales promotions significantly affects the intent to use BRT Trans Semarang, with a significance value of 0.000 (<0.05). Additionally, exposure to online customer reviews on Instagram also significantly influences the intent to use BRT Trans Semarang, with a significance value of 0.000 (<0.05).